2000
DOI: 10.1038/sj.ijo.0801086
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat loss evaluated by total body magnetic resonance imaging in obese women operated with laparascopic adjustable silicone gastric banding

Abstract: OBJECTIVE: To investigate the changes of visceral fat, as compared with total and subcutaneous adipose tissue (AT) in obese patients operated with laparascopic adjustable silicone gastric banding (LAP-BAND). SUBJECTS: Six premenopausal morbid obese (body mass index range: 41.4 ± 44.2 kgam 2 ) women, aged 38 ± 42 y, operated with LAP-BAND, evaluated before, 8 weeks after, and 24 weeks after surgery. MEASUREMENTS: Fat distribution was analysed by total body multi-slices MRI. Total AT, gluteo-femoral subcutaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 38 publications
6
47
1
Order By: Relevance
“…In women, the most consistent predictor of changes in VAT seems to be changes in body weight. This latter observation is in agreement with another recent study that demonstrated that body weight change was the only significant correlate of changes in VAT in a small sample of morbid obese women after laparascopic surgery (Busetto et al, 2000). These results should however be interpreted with caution since some studies have also shown that significant changes in VAT can occur with very small changes in body weight when exercise is part of the intervention (Mourier et al, 1997;Schwartz et al, 1991;Thomas et al, 2000;Thong et al, 2000;Treuth et al, 1995).…”
Section: Dependent Variablesupporting
confidence: 90%
“…In women, the most consistent predictor of changes in VAT seems to be changes in body weight. This latter observation is in agreement with another recent study that demonstrated that body weight change was the only significant correlate of changes in VAT in a small sample of morbid obese women after laparascopic surgery (Busetto et al, 2000). These results should however be interpreted with caution since some studies have also shown that significant changes in VAT can occur with very small changes in body weight when exercise is part of the intervention (Mourier et al, 1997;Schwartz et al, 1991;Thomas et al, 2000;Thong et al, 2000;Treuth et al, 1995).…”
Section: Dependent Variablesupporting
confidence: 90%
“…TAT was calculated by adding SAT and VAT (TAT ¼ SAT þ VAT); therefore, some small intramuscular deposits of adipose tissue were not accounted for. Similar to other published reports, 5,7,18,22,25,29,[33][34][35][36][37][40][41][42][43][44][45]47,[49][50][51][52][53][54][55][56][57][58][59][60][61][62][63] VAT and SAT were not further subdivided.…”
Section: Features Examinedsupporting
confidence: 78%
“…It is clear from these regression analyses, and in studies with multiple time points 59,64,65 that preferential loss of visceral fat is greatest during initial modest weight loss (Figures 1b, 3 and 4). Furthermore, extrapolation of the regression lines in Figures 3 and 4 leads to speculation that measurements of abdominal fat loss made after about 20% weight loss may start to show preferential loss of SAT or retention of VAT.…”
Section: Discussionmentioning
confidence: 77%
“…The limited data we currently have from surgical weight loss studies are inconsistent and serial measures following long term sustained weight loss are recommended. [62][63][64][65] The metabolic disturbances associated with visceral obesity are reflected in numerous clinical observations. In the 'Portal hypothesis' it is suggested that the proximity of VAT lipolysis, hormone and cytokine production upstream from the liver exacerbates hepatic insulin resistance and increases glucose output.…”
Section: Discussionmentioning
confidence: 99%